MENGELOLA HUBUNGAN PEMERINTAH PUSAT DENGAN PEMERINTAHAN DAERAH YANG EFEKTIF DAN EFISIEN DALAM POLITIK DESENTRALISASI - Kausar Ali Saleh (Universitas Nasional, 2017)
Within the framework of the politics of decentralization in the Era of political Reform beginning in 1998, authorization of several responsibilities in the hands of local governments across Indonesia is very crucial given the limited capacity in terms of human resources vis-à-vis the huge number of districts and municipalities in the country. The study makes an account of the relationship between cental government in Jakarta and local governments to look into the effectiveness and efficiency of running the good governance in macro politics perspective. The study finds that in the course of time, the policy to put sronger authority of governors by the enactment of the Law No. 23 2014 is ensuring Indonesia’s strong integrity of the territory of the country with vast and huge numbers of archipelagic country.